PEMBERDAYAAN PEREMPUAN MELALUI PENGUATAN UMKM OPAK GUNA MENINGKATKAN PEREKONOMIAN KELUARGA DI DESA SUGIH WARAS - Olivia Ayu Wandari; Dea Altulla Sadia; Tia Rachmawati; Muhammad Fadhil Ramadhan; Widya Anggraini; Yanto Yanto (CV. Denasya Smart Publisher, 2026)
Local-based enterprises in rural areas play a significant role in supporting household income, particularly those managed by women.. One example is the cassava cracker (opak singkong) business in Sugih Waras Village, which is run independently as a home-based business. This study aims to examine how strengthening the cassava cracker business can improve women’s skills and economic independence. The research used a qualitative approach through observation and direct interviews with the business owner. The findings reveal that the cassava cracker business contributes to household income, although it faces challenges such as inconsistent production, basic packaging, and limited marketing reach.. Through mentoring activities, the business owner began to understand the importance of maintaining product quality, improving packaging, and planning better marketing strategies. Business strengthening not only improves the product but also increases women’s confidence and ability to manage their business. With more organized management and continuous support, the cassava cracker business has the potential to grow and contribute more significantly to household and village economic development.